2017
DOI: 10.1515/amma-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Signalling Pathways: A Short Review and Specific Roles in Bone Biochemistry

Abstract: As musculoskeletal diseases become an emerging healthcare problem worldwide, profound and comprehensive research has been focused on the biochemistry of bone metabolism in the past decades. Wnt signalling, one of the novel described pathways influencing bone metabolism from the early stages of tissue development, has been recently in the centre of attention. Several Wnt ligands are implied in bone forming pathways via canonical (β-catenin dependent) and non-canonical (β-catenin independent) signalling. Osteopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Some researchers report that Wnt route plays an important role in bone formation. This pathway contains a large protein complex that transmits receptors from the cell surface to the genome [10]. Other studies have shown that inhibitors of this pathway, including sclerostin and dkk1, contribute to inhibition of bone metabolism and even osteoporosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers report that Wnt route plays an important role in bone formation. This pathway contains a large protein complex that transmits receptors from the cell surface to the genome [10]. Other studies have shown that inhibitors of this pathway, including sclerostin and dkk1, contribute to inhibition of bone metabolism and even osteoporosis [11,12].…”
Section: Introductionmentioning
confidence: 99%